PEMANFAATAN METODE KUANTITATIF UNTUK KELAYAKAN BIAYA DALAM AKUNTANSI - Lydiawati Soelaiman (Universitas Bunda Mulia, 2017)
There are many branch of science using statistics. Since Statistics is an important tool on decision making in many conditions, it could give advantages in accounting technique. In accounting, quantitative method used to bring reasonable price based on economic condition. Based on this assumption, a study was conducted in Jakarta on construction cost prediction and its correlation to inflation variable. The output shows that there is a correlation between those two variables in linear manner. Further analysis gives a confidence interval of the correlation equation. This should be used to makes a decision, whether an establish price is reliable or not in a specific interval. The study shows that a reasonable price in construction project lays on a range depends on the number inflation index in a particular time. It also shows that a proper quantitative method could be used as a tool in an accounting process. Keywords: Quantitative method, Inflation index, Construction cost, Correlation